Blue Carbon Degradation on Coral Reefs as Impact of Climate Change: Case Study at Samalona Island, Makassar City, South Sulawesi - Andi Siti Nur Azizah Al Faidi; Dwisha Aprilia Resky; A. Firdhlan Alivaiz; Almira Izzah Fawziyah Nadjib; Zein Abiya Devara; Dedi Rimantho (Buletin Oseanografi Marina, 2025)
Climate change is one of the global environmental hazards that can threaten humans and nature. Climate change can affect changes in temperature and rainfall. This research aims to estimate how much blue carbon potential can be absorbed by coral reefs on Samalona Island, and the effect on climate change. The collection of climate data for the last five years and Live Coral data for the last four years sourced from previous studies, added with field observations to obtain Live Coral data using the quadrat transect method. The identification results showed that there were 33,22% Live Coral, 50,56% Dead Coral, 7,44% Others, 8,78% Algae. To determine the blue carbon value, by multiplying the Live Coral data by the area of Samalona Island. The results are converted into square meters and multiplied by 7,72 x 10^-5 kg/m², this is the blue carbon value of Acropora Aspera. To determine the effect, simple regression was used with SPSS software. The results found that the interpretation value of blue carbon on temperature is 0,666 and on rainfall is 0,264, which shows that the relationship between blue carbon and temperature is strong and weak on rainfall.